SOSIALISASI PENGELOLAAN ADMINISTRASI DESA BERBASIS DIGITAL DI DESA SUMERTA KELOD, KOTA DENPASAR - I Putu Adi Permana Putra; I Gusti Ayu Agung Yuliartika Dewi; I Gede Agus Wibawa (Politeknik Negeri Sriwijaya, 2023)
The results of field observations carried out at the service locus objectively found that the problems being faced by Sumerta Kelod Village, Denpasar City, regarding digital-based village government administration This was explained by village officials: since the 2020 COVID-19 pandemic, village administration data has not been organized and visible on the village website, so efforts or steps are needed to realize digitally integrated village government administration management. Based on these issues, efforts and steps need to be taken, starting with the socialization and development of village government administration. This community service program is carried out by a team of public administration lecturers, with a focus on developing village administration. The objectives of this socialization and coaching are: 1) providing education and understanding to village officials regarding digital-based village administration management; 2) optimizing the use of technology in providing public services to the community; and 3) realizing good governance in digital-based village government. Keywords: Management, Villages Government of Administration, Digitalization